Associations between cognitive skills and white matter integrity at age 5 years: a diffusion-weighted imaging study - Dangal, Anjan (My University, 2025)
The development of cognitive skills in children is crucial for physical and mental health, as well as productive life in adulthood. The growth of specific cognitive skills, with respect to increasing age, reflects healthy brain maturation and normal neurodevelopment processes. Cognitive tasks require an integrated co-ordination of different cerebral regions, white matter tracts and deep brain structures, working as a network. Studying the relationship between cognitive abilities and white matter maturation in children can provide insights into the involvement of white matter in the cognition network. However, studies on relationship between white matter integrity and nonverbal cognitive skills in early childhood are very limited. This study investigated the relationship between nonverbal cognitive skills and white matter integrity in 137 healthy 5-year-old children from the FinnBrain Birth Cohort Study. Fractional anisotropy (FA), derived from diffusion tensor imaging (DTI), was used as an indicator of white matter integrity. Nonverbal cognitive ability was assessed using the Block Design and Matrix Reasoning subtests of the Wechsler Preschool and Primary Scale of Intelligence (WPPSI-III), from which an estimated Performance Intelligence Quotient (PIQ) score was calculated. Voxel-wise statistical analysis of Tract Based Spatial Statistics (TBSS) derived FA skeleton data was conducted using FMRIB Software Library (FSL)’s tool: randomise. Results showed no significant associations between PIQ scores and white matter integrity. These findings align with previous studies conducted on older children and children with mixed age groups. In addition, it provides novel insights into a 5-year-old cohort, which were previously unavailable. Our results suggests that white matter integrity and evolving nonverbal cognitive skills does not seem to have relationship at age 5. Longitudinal research is needed to fully understand the relationship between white matter integrity and nonverbal cognitive abilities.
Keywords: Nonverbal cognitive skills, white matter integrity, PIQ, TBSS, WPPSI-III